1997
DOI: 10.1080/00039899709602220
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Residential Exposure to Hazardous Wastes and Risk of Central Nervous System and Musculoskeletal Birth Defects

Abstract: The authors used a case-control design to evaluate the risk of central nervous system and musculoskeletal birth defects relative to exposure to solvents, metal, and pesticide contaminants from hazardous waste sites. Cases included 473 central-nervous-system-defect births and 3305 musculoskeletal-defect births to residents of 18 counties in New York State; controls comprised 12,436 randomly chosen normal births. For each address at birth, the authors assigned a probability of exposure to solvents, metals, and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
1
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 9 publications
1
40
1
1
Order By: Relevance
“…However, Stehr-Green et al (13) reported that people living near waste sites had a higher average serum PCB level, and a greater percentage had PCB levels elevated with respect to the average U.S. level. Geschwind et al (14) and Dolk et al (15) have both reported elevated incidence of birth defects in individuals living near hazardous waste sites, but other studies have not seen this relationship (16).…”
Section: Discussionmentioning
confidence: 94%
“…However, Stehr-Green et al (13) reported that people living near waste sites had a higher average serum PCB level, and a greater percentage had PCB levels elevated with respect to the average U.S. level. Geschwind et al (14) and Dolk et al (15) have both reported elevated incidence of birth defects in individuals living near hazardous waste sites, but other studies have not seen this relationship (16).…”
Section: Discussionmentioning
confidence: 94%
“…A dose-response relationship (higher risks with higher exposure) was reported between estimated hazard potential of the site and risk of malformation, adding support to a possible causal relationship. However, a follow-up study of Geschwind's findings (62) found no relation between two selected types of malformations (central nervous system and musculoskeletal) and living near a hazardous waste disposal site. The study did report an increased risk of central nervous system defects for those living near solvent-or metalemitting industrial facilities.…”
Section: Epidemiologic Studies On Health Effects Of Landfill Sitesmentioning
confidence: 99%
“…ambient air monitoring) have been linked to live birth registries to assess the impact of air pollution on infant birth size (Wilhelm & Ritz, 2003), gestation (Ritz et al, 2000), or birth defects (Ritz et al, 2002). Similarly, geographic proximity to hazardous waste sites (Marshall et al, 1997) and the consumption of PCB-contaminated fish (Mendola et al, 2005) have been associated with birth defects using a state birth defects registry.…”
Section: Descriptive Designsmentioning
confidence: 99%